2023
DOI: 10.1111/ele.14196
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term trajectories of non‐native vegetation on islands globally

Abstract: Human‐mediated changes in island vegetation are, among others, largely caused by the introduction and establishment of non‐native species. However, data on past changes in non‐native plant species abundance that predate historical documentation and censuses are scarce. Islands are among the few places where we can track human arrival in natural systems allowing us to reveal changes in vegetation dynamics with the arrival of non‐native species. We matched fossil pollen data with botanical status information (na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 94 publications
(121 reference statements)
0
6
0
Order By: Relevance
“…3b ) is likely caused by novel anthropogenic drivers. Within the novel drivers of change, burning (for example, as a part of agricultural activities), introduction of non-native taxa and extinctions or extirpations (of both fauna and flora) have been shown to impact island ecosystems 11 , 30 , 40 . First, the increased occurrence and intensity of disturbances is linked to anthropogenic modification of the islands’ landscapes, for example, as a consequence of slash and burn techniques 11 , 36 , 41 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…3b ) is likely caused by novel anthropogenic drivers. Within the novel drivers of change, burning (for example, as a part of agricultural activities), introduction of non-native taxa and extinctions or extirpations (of both fauna and flora) have been shown to impact island ecosystems 11 , 30 , 40 . First, the increased occurrence and intensity of disturbances is linked to anthropogenic modification of the islands’ landscapes, for example, as a consequence of slash and burn techniques 11 , 36 , 41 .…”
Section: Discussionmentioning
confidence: 99%
“…It has also been shown that intense human impacts, such as urbanization and intensively managed agroforestry plantations, can lead to an increase in globally distributed taxa and therefore biotic homogenization 42 , 43 . Second, it is important to highlight that fossil pollen records from islands have also shown that non-native plant introductions increased within the past 1,000 years, suggesting potentially long-term presence of widely distributed species 30 . For example, non-native species introduced to multiple islands by people may have contributed to increased similarity among island ecosystems 30 , 44 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The introduction of non-native species poses considerable threats to islands' biodiversity (Dawson et al, 2017;Kueffer et al, 2010;Lonsdale, 1999;Pyšek & Richardson, 2006;Walentowitz et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Species numbers on islands have been increasing and are predicted to continue to rise in the future, mainly due to the accidental and deliberate introduction of non-native species (also referred to as alien species) by humans (Sax et al, 2002;Seebens et al, 2017;Walentowitz et al, 2023). In consequence, total plant species richness on some islands has more than doubled, and the number of non-native species exceeds the number of native species (Essl et al, 2019).…”
Section: Introductionmentioning
confidence: 99%